The Effect of Work-Life Balance and Workload on Employee Performance - Mezaluna MEZALUNA; Jurana JURANA; Abd. PATTAWE; Latifa LATIFA (International Journal of Environmental, Sustainability, and Social Science (IJESSS), 2026)
Maintaining optimal Employee Performance relies heavily on Work-life Balance and reasonable Workload. An unbalanced Workload can hinder productivity, while a healthy Work-life Balance can encourage more effective and efficient performance. To assess how Employee Performance at BPJS Kesehatan Palu Branch Office is affected by Workload and Work-life Balance. This research uses quantitative methodology, by collecting data from 30 respondents through questionnaires and Google forms and then analyzed using WarpPLS 7.0. The results revealed that Employee Performance is significantly affected by the balance between Work-life Balance and Workload. By examining the impact of Workload and Work-life Balance simultaneously in the public service sector, this study offers a new perspective.